Belle et le Bête - Charles Perrault (Western Publishing Co., 1992)
Through her great capacity to love, a kind and beautiful maid releases a handsome prince from the spell which has made him an ugly beast.
Métadonnées bibliographiques issues d Open Library
Keywords: open library; histoire; Géographie; livre; Nursery rhymes; france; Children's stories; French; Fairy tales